Money and housing: evidence for the euro area and the US - Claus Greiber; Ralph Setzer (Deutsche Bundesbank, 2007)
This paper examines the relation between money and housing variables in the euro area and in the US. Our empirical model is based on a standard money demand relation which is augmented by housing market variables. In doing so, co-integrated money demand relationships can be established for both the euro area and the US. Furthermore, we find evidence for asset inflation channels, that is, liquidity fuels housing market developments.
Keywords: E52; E41; 330; money demand; asset inflation; housing; wealth; Immobilienpreis; Geldnachfrage; Geldmenge; Immobilienmarkt; Schätzung; EU-Staaten; USA